IS EARNINGS PERSISTENCE STILL RELEVANT? EVALUATING ASSET GROWTH AND DIVIDEND POLICY ON FIRM VALUE - Audrey Ekaviany Juniarti Mahal; Suwandi Ng; Paulus Tangke (AJAR, 2026)
The purpose of this study is to analyze the impact of Asset growth and dividend policy on increasing firm value through earnings persistence. The theories used are agency theory and stakeholder theory.This study uses secondary data in the form of annual reports from companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. The sample consists of data from 123 companies over a three-year period, selected using purposive sampling. The results of this study indicate that Asset growth has a negative but insignificant effect on earnings persistence, while dividend policy has a negative but insignificant effect on earnings persistence. Asset growth has a negative but insignificant effect on firm value. Dividend policy has a positive but insignificant effect on firm value, and earnings persistence has a significant negative effect on firm value. These findings also indicate that earnings persistence does not moderates the effect of Asset growth on firm value and earnings persistence does not moderate the effect of dividend policy on firm value